Non intentional burns in children: Analyzing prevention and acute treatment in a highly developed country. Issue 8 (December 2019) - Moehrlen, Theres; Landolt, Markus A.; Meuli, Martin; Moehrlen, Ueli
Highlights: Proportion of foreigners is age dependent in burn injuries. First aid treatment is poor in our study population. Estimation of TBSA is mostly overestimated during initial medical assessment. Burn etiology has a major impact on cosmetic results. Several suggestions for prevention campaigns. Abstract: The objective of this study was to evaluate where and when pediatric burn injuries occurred. Furthermore the quality of first aid treatment, ratio of skin grafting and length of hospital stay were evaluated. The patient records of 749 children with acute burns admitted to the University Children's Hospital of Zurich, Switzerland, were retrospectively reviewed over an 11-year period. Burn injuries in children with an immigrant background were overrepresented in our study population, whereby the proportion of immigrants decreased with rising age. Sixty-five percent of all patients received some form of first aid. Of those 4.5% did not comply with the current guidelines. Furthermore initial assessment of total body surface area (TBSA) by the first line physician was overestimated in 76% of cases. Flame injuries occurred mainly in summertime in outdoor settings and needed significant more often skin grafts than scalds, which mainly occurred indoors and in wintertime. As a result, patients with flame injuries had to stay significantly longer in hospital (flames: 21 days (range: 1–259 days; median: 30; interquartile range (IQR): 30) versus scalds: 7 days (range: 1–130 days; median: 7; IQR: 12); p < 0.001). Furthermore high voltage injuries often resulted in lower-leg amputations (n = 3; 43%). Based on these facts, targets for the improvement of a prevention campaign and the treatment for burned children were named.